Laser Decontamination of a Fuel-Element Surface from Uranium-Plutonium Fuel Particles; Atomic Energy; Vol. 131, iss. 1 - Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Pushkarev A. I. Aleksandr Ivanovich; Tuksov I. V. Iljya Vladimirovich; Lukin A. V. Anton Vyacheslavovich; Khan V. A. Valery Alekseevich; Khorokhorin D. M. Dmitry Mikhaylovich; Eremeev R. S. Roman Semyonovich; Lychagin D. V. Dmitry Vasiljevich (2021, 2021)
Title screen